2021
DOI: 10.3390/ijerph18126460
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing an EMG Biofeedback Device for Gait Rehabilitation: Development, Validity and Reliability

Abstract: Gait impairment often limits physical activity and negatively impacts quality of life. EMG-Biofeedback (EMG-BFB), one of the more effective interventions for improving gait impairment, has been limited to laboratory use due to system costs and technical requirements, and has therefore not been tested on a larger scale. In our research, we aimed to develop and validate a cost-effective, commercially available EMG-BFB device for home- and community-based use. We began by repurposing mTrigger® (TJM Electronics, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Interestingly, studies that used more than one system at a time ( 79 , 80 ) revealed a focus for technology fusion applied to future research data collection as the technology improves. Both studies demonstrated the value of using smartphone application software for data filtering, processing, and outputs, providing a successful, user-friendly tool for reduced use of laboratory-based equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies that used more than one system at a time ( 79 , 80 ) revealed a focus for technology fusion applied to future research data collection as the technology improves. Both studies demonstrated the value of using smartphone application software for data filtering, processing, and outputs, providing a successful, user-friendly tool for reduced use of laboratory-based equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Implications for clinical applications of handwriting research Understanding these relationships in a typically developing cohort will then allow future studies to evaluate individuals with different types of disabilities or conditions and unravel the complexities of the pauses, to ascertain whether there are deficits in motor planning, executive function, or cognitive task overload. Additionally, it is possible to collect electromyography (EMG) data to monitor muscular activity in conjunction with biomechanical analysis of handwriting and cortical activity to further dissect if problems are muscular in nature and can benefit from specific muscle feedback as has been done in handwriting and other skills [59] [60]. Handwriting difficulties are common in populations such as DCD, ADHD, and others where manual dexterity is impaired and can have lasting consequences on academic achievement and self-esteem [61].…”
Section: Discussionmentioning
confidence: 99%
“… Application in medical. ( a ) Use FMG and machine learning techniques to differentiate between grasping and no grasping [ 169 ]; ( b ) textile electrodes integrated with a clothing belt for EIT lung imaging [ 170 ]; ( c ) assisted rehabilitation design of 3D printed hand exoskeleton based on FMG control [ 171 ]; ( d ) EMG biofeedback device for gait rehabilitation [ 172 ]; ( e ) detection of changes in lower extremity muscle impedance properties immediately after functional electrical stimulation-assisted cycling training in chronic stroke survivors [ 173 ]; ( f ) an evaluation of spontaneous respiratory idiopathic pulmonary fibrosis using EIT [ 174 ]. …”
Section: Figurementioning
confidence: 99%